THE EFFECTS OF CORRECTIVE FEEDBACK TO THE STUDENTS’ GRAMMATICAL CONSTRUCTION ON PARAGRAPH WRITING CLASS - Dina Merris Maya Sari (STKIP Persada Khatulistiwa Sintang, 2019)
Writing is one of the most important skill to mastery English. But there are many students get difficulties in writing. They worried when they make errors in their writing. To overcome this problem, the researcher uses corrective feedback. Here, corrective feedback is used to revise the students’ writing. It is hoped by this technique, the students can revise to make better and correct in writing. Based on the reason above, the objective of the study is “to know the effectiveness of using corrective feedback in paragraph writing class”. This research is experimental studies and the researcher uses quantitative research. In experimental quantitative research, there are two groups of students participated in the study, control and experimental group. The subject of this research is the students 2018 English Education Department. The data collection technique is by testing writing composition and the data analyze technique used t-test calculated by SPSS Statistic 17.0 to find out the difference between students’ pretest and posttest scores of experimental and control group. This result show that the experimental group which is taught by using corrective feedback get high scores than the control group which is not taught by using corrective feedback.